APROXIMACIÓN A LA REPRESENTACIÓN EN XML DE OBJETOS DICOM PARA FOTOGRAFÍA MÉDICA DIGITAL (2013)
El estándar DICOM (Digital Imaging and Communication in Medicine) es un protocolo no propietario para el intercambio de información médica. DICOM representa y define la información de objetos del mundo real tales como una resonancia magnética (MRI), una tomografía computarizada (CT) y una fotografía médica digital (VL Photographic), por medio de definiciones de objeto de información llamados IOD. El presente artículo describe una metodología para representar el IOD de una fotografía médica digital de luz visible (VL Photographic Image) por intermedio de documentos XML Schema. Estos documentos se utilizan en la creación y validación de documentos XML para representar información clínica técnica asociada a fotografías médicas digitales para su posterior implementación en una aplicación web de teledermatología.Abstract: DICOM standard (Digital Imaging and Communication in Medicine) is a non-proprietary protocol for the medical exchange information. DICOM represents and defines the information of real world objects like a magnetic resonance image (MRI), a computerized axial tomography and a digital medical photography (VL photographic), through information object definitions called IOD. The present article describes a methodology to represent the IOD of a digital medical photography of visible light (VL Photographic Image) through XML Schema documents. These documents were used in the creation and validation of XML documents to represent digital medical photographies compiling clinical and technical information for their later implementation in a teledermatology application.